Method for pure physical separation of all components of waste lithium ion battery

Through the pure physical separation method of full-components, combined with mechanical crushing, air selection, magnetic separation, water phase peeling and roller pressing pyrolysis processes, the problem of poor quality of waste lithium-ion batteries is solved, the recycling of high-purity positive electrode powder and the effective utilization of each component is achieved, and the recycling cost and pollution risk is reduced.

CN119657601AActive Publication Date: 2025-03-21CENT SOUTH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411885141.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, the crushing-separation method of used lithium-ion batteries is difficult to obtain raw material quality that meets the needs of direct regeneration, and there are problems such as high impurity content, low recovery rate and ineffective use of materials.

Method used

The full-component pure physical separation method is adopted, and the diaphragm and iron shell are removed by mechanical crushing. Combined with the aqueous phase peeling and rolling pyrolysis process, the high-purity separation of the positive electrode powder and the recycling of each component are achieved in steps.

Benefits of technology

It realizes high-purity recycling of the positive electrode powder of waste lithium-ion batteries and the effective recycling of various components, avoids the damage and pollution of crystal phase structure introduced by chemical methods, and reduces the recycling cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657601A_ABST
    Figure CN119657601A_ABST
Patent Text Reader

Abstract

The invention discloses a pure physical separation method for all components of a waste lithium ion battery, which comprises the following steps: mechanically crushing the waste lithium ion battery into a large-size crushed material, removing a diaphragm by winnowing, and removing an iron shell by magnetic separation to obtain a positive and negative electrode mixture; the positive and negative electrode mixture is subjected to water phase stripping of negative electrode powder and primary color sorting separation of copper foil to obtain a positive electrode plate; the positive pole piece is sequentially subjected to rolling pyrolysis, low-speed jet milling and secondary color sorting separation, and then high-purity positive pole powder and aluminum foil are obtained. The positive electrode powder obtained through the method is high in purity, and all the components can be recycled through step-by-step removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for purely physically separating all components of waste lithium-ion batteries, and in particular to a method for obtaining ultra-high-purity electrode materials from mechanically crushed lithium-ion batteries by a purely physical method, belonging to the technical field of battery recycling. Background Art

[0002] The efficient treatment of waste batteries is a key step in the closed loop of the new energy industry. The current comprehensive recycling of lithium-ion batteries mainly includes wet recycling and direct regeneration processes. Among them, the wet recycling process mainly realizes the efficient recycling of waste battery materials by turning materials into elements, but the process consumes a large amount of acid and alkali and produces a large amount of three waste pollutants. The direct regeneration method is a method that directly converts waste materials into materials, greatly shortens the process, and improves the efficiency of resource recycling. It is currently an efficient new recycling technology. However, the direct regeneration method has high requirements for the purity of raw materials, among which the copper content needs to be less than 200ppm and the aluminum content needs to be less than 3000ppm. The current process for obtaining direct regeneration powder mainly comes from manual disassembly, which is inefficient and harmful to life. The traditional mechanical crushing-separation method is difficult to obtain the raw material quality that meets the needs of direct regeneration. Gravity selection is to achieve effective separation of various phases through the density differences between different substances, with the advantages of low cost, low energy consumption, and great scale prospects.

[0003] Therefore, there is an urgent need to develop a method for re-selecting and separating all components of waste lithium-ion batteries. Summary of the invention

[0004] In view of the problems in the prior art that the impurity content of the positive electrode powder material obtained by the crushing-separation method of waste lithium batteries is too high to be repaired, the recovery rate is low, and other components cannot be utilized, the purpose of the present invention is to provide a method for purely physical separation of all components of waste lithium-ion batteries. The positive electrode powder obtained by this method has high purity, and each component can be recycled by step-by-step removal, avoiding the problems in the prior art of introducing chemical methods to damage the crystal phase structure of the material, introducing copper and aluminum impurity components, and causing the generation of waste acid and waste liquid.

[0005] In order to achieve the above technical objectives, the present invention provides a method for purely physical separation of all components of waste lithium-ion batteries, which comprises the following steps: mechanically crushing the waste lithium-ion batteries into large-scale crushed materials, removing the diaphragm by air separation, and removing the iron shell by magnetic separation to obtain a positive and negative electrode mixture; the positive and negative electrode mixture adopts aqueous phase to strip the negative electrode powder, and the first color separation of the copper foil to obtain a positive electrode sheet mixture; the positive electrode sheet mixture is sequentially subjected to roller pyrolysis, low-speed air flow milling, and a second color separation to obtain a high-purity positive electrode powder and aluminum foil.

[0006] Most of the pole piece mixtures processed in the current waste battery processing process are for low-scale pole pieces. The positive electrode materials on such pole pieces are conducive to pyrolysis and stripping, but the recycling path is relatively rough, and the recovered positive and negative electrode raw materials are of low purity, which has a great impact on the wet leaching and direct regeneration in the later stage, and it is difficult to achieve high-quality recycling of positive and negative electrode materials. The present invention cleverly combines the aqueous phase stripping process and the roller pyrolysis process with the existing process, purely physically separates the waste lithium-ion batteries, and achieves the effect of recycling all components in steps. Specifically, the present invention first crushes the waste lithium-ion batteries into large-scale crushed materials, and removes the diaphragm and iron shell by air separation and magnetic separation, so as to obtain relatively pure positive and negative electrode mixtures, and crushing into large-scale pole piece materials is conducive to the subsequent aqueous phase stripping. In view of the characteristics of using water-soluble binders in the negative electrode sheets of waste lithium-ion batteries, the present invention utilizes water phase stripping to not only realize the negative electrode material falling off from the negative electrode sheet, but also obtain relatively pure yellow copper foil, thereby increasing the color difference between the positive electrode sheet and the negative electrode sheet through water phase stripping, which is further conducive to improving the accuracy of subsequent color sorting and separation. In addition, compared with the operation of long-term pyrolysis or acid washing to de-powder the positive electrode material in the traditional process, the combined process of roller hot pressing and low-speed airflow milling of the present invention can rapidly degrade PVDF through the action of high temperature and pressure in a short time, and the fluoride and carbide formed by pyrolysis are volatilized and removed, which not only ensures the purity of the material but also reduces the damage to the electrode sheet, and greatly improves the de-powdering efficiency of the positive electrode material through low-speed airflow milling, and finally, the efficient separation of the positive electrode material and the aluminum foil can be achieved through a simple color sorting and separation process.

[0007] As a preferred solution, the waste lithium-ion batteries are mainly derived from one of lithium iron phosphate batteries, ternary batteries and lithium cobalt oxide batteries purchased on the market.

[0008] As a preferred solution, the scale of the large-sized crushed material is 5mm to 5cm. The large scale of the crushed material of the present invention can effectively avoid the entrainment of fine impurity components, the winding and folding of small pole pieces, and is conducive to the subsequent control of material purity.

[0009] As a preferred solution, the air selection speed is 4 m s -1 ~10ms -1 . In the present invention, the density of the diaphragm in the battery crushed material is relatively light, and the density difference between the diaphragm and the positive and negative electrode mixture is utilized to remove the diaphragm in the crushed material through the action of airflow. If the air selection speed is too low, the diaphragm may not be effectively taken away, and part of the diaphragm remains in the positive and negative electrode mixture, affecting the purity of the material in the subsequent processing steps; when the air selection speed is too high, some smaller particles in the positive and negative electrode mixture will be entrained by the airflow due to the high wind speed, and mixed into the separated diaphragm light material, causing material loss and reducing the recovery rate of the positive and negative electrode mixture.

[0010] As a preferred solution, the magnetic induction intensity of the magnetic separation is 1.0 T to 3.0 T. Within the preferred magnetic separation intensity range of the present invention, the iron shell in the positive and negative electrode mixture can be effectively removed.

[0011] As a preferred solution, the aqueous phase stripping is ultrasonic aqueous phase stripping or stirring aqueous phase stripping, and the aqueous phase stripping uses a mixed solution of water and ethanol as a stripping solution. In the present invention, due to the strong hydrophobicity of graphite, it is difficult for the graphite pole piece to be highly dispersed in the aqueous phase solution, resulting in poor contact between the graphite pole piece and the aqueous phase, and it is difficult to effectively strip the graphite powder from the negative electrode pole piece; and using a mixed solution of water and ethanol as a stripping solution can significantly increase the stripping effect.

[0012] As a preferred solution, the positive and negative electrode mixture is filtered by using a sieve with a mesh size of 1 to 4 mm to remove the negative electrode powder by aqueous phase. The selection of the mesh size of the present invention comprehensively considers the size of the negative electrode powder, the positive electrode sheet mixture and the copper foil to achieve the separation of the negative electrode powder, the positive electrode sheet mixture and the copper foil.

[0013] As a preferred solution, the roller pyrolysis conditions are: roller heating, roller temperature is 1000-1500°C, rotation speed is 2-5 min -1 The roller pyrolysis of the present invention mainly utilizes the effect of high temperature and pressure to make the binder PVDF ineffective. During the roller pyrolysis process, if the temperature is too high and the time is too long, the crystalline structure of the positive electrode material will be damaged, which is not conducive to the subsequent repair process. At the same time, the fluorine-containing substances produced by PVDF during the pyrolysis process may react with the material, resulting in the introduction of fluorine impurity elements, causing the fluorine content to exceed the standard in the subsequent regeneration process, and the material performance will seriously decline; if the roller temperature is too low and the time is too short, the PVDF pyrolysis will be incomplete, and the carbide produced after the pyrolysis cannot be volatilized, resulting in a decrease in the recovery rate and purity of the positive electrode sheet, and a decrease in the recovery efficiency of the positive electrode material.

[0014] As a preferred solution, the grinding rate of the low-speed airflow mill is 3 to 8 m / s. 3 min -1 The higher the jet mill speed, the lower the efficiency of positive electrode powder removal and the lower the recovery efficiency of positive electrode powder; if the jet mill speed is too fast, it will cause the pole piece aluminum impurities to be introduced into the positive electrode powder, reducing the activity of the positive electrode material.

[0015] As a preferred solution, the first color sorting and separation and the second color sorting and separation are both implemented by a color sorter, and the first color sorting and separation sets the identification color to yellow; the second color sorting and separation sets the identification color to white.

[0016] The present invention involves large-scale mechanical crushing, drying and other processes, which are conventional operating processes in the prior art, and the purpose is to obtain a large-scale powder structure and remove excess moisture from the material.

[0017] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0018] 1) The present invention can realize the recycling of all components of waste lithium-ion batteries, which not only improves the recycling efficiency of resources, but also reduces pollution to the environment. The pure physical separation method is adopted to avoid the secondary pollution problem that may be caused by traditional chemical treatment methods, and also reduces the recycling cost.

[0019] 2) The present invention can significantly improve the recovery rate and purity of positive and negative electrode materials by combining the aqueous phase stripping process and the roller pyrolysis process, which is beneficial to subsequent wet leaching and direct regeneration.

[0020] 3) The combined process of roller hot pressing and low-speed airflow milling of the present invention can rapidly degrade PVDF by pyrolysis through the action of high temperature and pressure in a short period of time, and the fluoride and carbide formed by pyrolysis are volatilized and removed, which not only ensures the purity of the material but also reduces the damage to the electrode sheet, and the de-powdering efficiency of the positive electrode material is greatly improved by low-speed airflow milling.

[0021] 4) The method of the present invention is simple, low-cost, conducive to commercial production, and has high economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a flow chart of the technology for reselection and separation of all components of waste lithium-ion batteries.

[0023] Figure 2 The present invention is a process flow chart of the technology for gravity separation of all components of waste lithium-ion batteries. DETAILED DESCRIPTION

[0024] The following examples are only specific descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of implementation of the present invention. For ordinary technicians in the technical field, any improvements made without departing from the present invention should be deemed to be within the scope of protection of the present invention.

[0025] The waste lithium-ion batteries used in the present invention are mainly derived from any one of lithium iron phosphate batteries, ternary batteries, and lithium cobalt oxide batteries purchased on the market. According to the process roadmap and technical process, an embodiment is designed.

[0026] In the embodiment of the present invention, the first color sorting separation and the second color sorting separation are both achieved by a color sorter. The identification color of the first color sorting separation is set to yellow; the identification color of the second color sorting separation is set to white. The intensity of magnetic separation is 1.0T, and the volume ratio of water and ethanol in the stripping liquid used for aqueous phase stripping is 1:1.

[0027] Example 1 (Comparative Example)

[0028] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative pole pieces after mechanical crushing is 1 cm. The iron shell and other strong magnetic materials are removed by magnetic separation. The pole pieces are roller heated with a roller temperature of 1200℃ and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and the positive electrode material are further separated by color sorting (using a color sorter, and the color sorter is set to white) to obtain high-purity positive electrode material. The positive electrode material recovery rate is 53%, the positive electrode material purity is 47%, the graphite content is 52%, and the copper and aluminum impurity content is 1%.

[0029] Example 2 (Comparative Example)

[0030] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the subsequent positive electrode sheets are further added to a low-speed airflow mill at a grinding rate of 5m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting to obtain high-purity positive electrode material. The positive electrode material recovery rate is 12% and the purity is 92%.

[0031] Example 3

[0032] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1, strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 81% and the purity is 99.95%.

[0033] Example 4

[0034] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 5mm, and the crushed materials are physically selected by air at a rate of 7m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting to obtain high-purity positive electrode material. The positive electrode material recovery rate is 78% and the purity is 98.3%.

[0035] Example 5

[0036] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 5 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min-1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 72% and the purity is 99.95%.

[0037] Example 6

[0038] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 4 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 80% and the purity is 97%.

[0039] Example 7

[0040] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 10 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting to obtain high-purity positive electrode material. The positive electrode material recovery rate is 79% and the purity is 96%.

[0041] Example 8

[0042] The raw materials are retired ternary batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1, strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and stirred for enhanced separation. The stripped mixed solution is filtered through a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated through the first color separation, and the positive electrode sheet is subsequently roller heated with a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 72% and the purity is 99.95%.

[0043] Example 9

[0044] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered through a sieve with a mesh size of 1 mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated through the first color separation, and the positive electrode sheet is subsequently roller heated with a roller temperature of 1200°C and a rotation speed of 3 min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting to obtain high-purity positive electrode material. The positive electrode material recovery rate is 82% and the purity is 96%.

[0045] Example 10

[0046] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 4mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min-1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 74% and the purity is 99.95%.

[0047] Embodiment 11

[0048] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers. The roller temperature is 1000℃ and the rotation speed is 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 69% and the purity is 99.95%.

[0049] Example 12

[0050] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered through a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated through the first color separation, and the positive electrode sheet is subsequently roller heated with a roller temperature of 1500℃ and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 81% and the purity is 99.95%.

[0051] Example 13

[0052] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s-1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered through a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 2m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 76% and the purity is 99.95%.

[0053] Embodiment 14

[0054] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 5m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 5 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 80% and the purity is 99.95%.

[0055] Embodiment 15

[0056] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 3 m3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 73% and the purity is 99.95%.

[0057] Example 16

[0058] The raw material is retired lithium iron phosphate batteries, which come from a new energy enterprise in Zhejiang. The size of the positive and negative electrode pieces after mechanical crushing is 1 cm, and the crushed materials are physically selected by air at a rate of 7 m s -1 , strong magnetic materials such as iron shells are removed by magnetic separation, and the positive and negative electrode mixture is added to a water and ethanol solution, and separated by ultrasound. The mixed solution after stripping is filtered with a sieve with a mesh size of 3mm. The filtrate contains negative electrode powder material, and the upper layer contains positive electrode sheets and copper foil. The copper foil is separated by the first color separation, and the positive electrode sheet is subsequently heated by rollers at a roller temperature of 1200°C and a rotation speed of 3m min -1 The separated material is further fed into a low-speed jet mill at a grinding rate of 8 m 3 min -1 The de-powdered positive electrode sheet and positive electrode material are separated by a second color sorting process to obtain high-purity positive electrode material. The positive electrode material recovery rate is 81% and the purity is 99%.

[0059] Table 1 Separation conditions and effects of Examples 1 to 16

[0060]

[0061]

Claims

1. A method for purely physical separation of all components of waste lithium-ion batteries, characterized in that: After the waste lithium-ion batteries are mechanically crushed into large-scale crushed materials, the diaphragm is removed by air separation and the iron shell is removed by magnetic separation to obtain a positive and negative electrode mixture; the positive and negative electrode mixture is subjected to aqueous phase stripping of the negative electrode powder and the first color separation of the copper foil to obtain the positive electrode sheet; the positive electrode sheet is successively subjected to roller pyrolysis, low-speed air flow grinding, and a second color separation to obtain high-purity positive electrode powder and aluminum foil.

2. The method for pure physical separation of all components of waste lithium-ion batteries according to claim 1, characterized in that: The scale of the large-scale crushed material is 5mm to 5cm.

3. The method for pure physical separation of all components of waste lithium-ion batteries according to claim 2, characterized in that: The speed of the wind selection is 4 to 10 m s -1 .

4. A method for purely physical separation of all components of waste lithium-ion batteries according to claim 1 or 2, characterized in that: The magnetic induction intensity of the magnetic separation is 1.0T to 3.0T.

5. A method for purely physical separation of all components of waste lithium-ion batteries according to claim 1 or 2, characterized in that: The aqueous phase stripping is ultrasonic aqueous phase stripping or stirring aqueous phase stripping, and the aqueous phase stripping uses a mixed solution of water and ethanol as a stripping solution.

6. The method for purely physical separation of all components of waste lithium-ion batteries according to claim 5, characterized in that: The positive and negative electrode mixture is filtered by using a sieve with a mesh size of 1 to 4 mm to remove the negative electrode powder in the aqueous phase.

7. The method for purely physical separation of all components of waste lithium-ion batteries according to claim 6, characterized in that: The roller pyrolysis conditions are: roller heating, roller temperature is 1000-1500°C, and the rotation speed is 2-5 min -1 .

8. A method for purely physical separation of all components of waste lithium-ion batteries according to claim 1 or 7, characterized in that: The grinding rate of the low-speed airflow mill is 3 to 8 m / s. 3 min -1 .

9. The method for purely physical separation of all components of waste lithium-ion batteries according to claim 1, characterized in that: The first color sorting and separation and the second color sorting and separation are both implemented by a color sorter. The first color sorting and separation sets the identification color to yellow; the second color sorting and separation sets the identification color to white.

Citation Information

Patent Citations

  • Recycling process of positive electrode materials of waste batteries

    CN109326843A

  • Method for recovering valuable components of waste lithium ion batteries

    CN113999976A

  • Sorting method for recycling positive and negative electrode powder of waste lithium battery

    CN114147043A

  • Method for recycling all components of waste lithium battery

    CN114151802A

  • Method for recovering all-component material from waste lithium ion battery

    CN114639888A